Program Pengelolaan Penyakit Kronis Diabetes Mellitus sebagai Pencegahan Penyakit Degenerative Diabetes Mellitus, Dan Dampaknya Bagi Pekerja Di Indonesia - Dicky Permana Putra; Anita Rahmiwati; Yuanita Windusari; Novrikasari; Nur Alam Fajar (Syntax Literate, 2023)
The World Health Organization (WHO) estimates that the number of people with diabetes mellitus (DM) worldwide will increase rapidly to reach 21.3 million by 2030, an increase from 8.4 million in 2020. Workers are one of the groups most vulnerable to the risk of diabetes mellitus (DM). Almost all of the worker time is spent working indoors and doing only a few physical movements. This can lead to health problems. Due to the pressure brought on by their jobs, workers tend to engage in bad habits such as smoking, alcohol, and eating unhealthy foods, among others, which have an impact on their behavior and their lifestyle. The high level of stress experienced by para is the cause of this behavioural tendency. The impact of this behaviour makes workers vulnerable to diabetes mellitus (DM). Diabetes mellitus (DM) can appear suddenly without symptoms (silent killer). Workers must carry out health checks immediately to find out and prevent diseases such as diabetes mellitus (DM) early. Because Diabetes Mellitus tends to increase and begin to appear at a younger age of workers, companies must plan and optimize the management of screening examinations early for workers to detect the incidence of Diabetes Mellitus through occupational health activities, especially by involving all workers so that the risk of Diabetes Mellitus events with risk factors that already exist in each worker can be predicted early through The Chronic Disease Management Program (PROLANIS) has a positive impact in managing type 2 Diabetes Mellitus (DM) in the prevention of degenerative diseases in Indonesia. However, there are still several obstacles, such as inappropriate schedules, lack of public awareness, and the need for role models and peer group support in running this program. Therefore, efforts to optimize the PROLANIS DM program and increase the understanding of participants and the public about the importance of DM prevention are very important to overcome this problem and its impact on Indonesian workers in the prevention of degenerative NCDs that can prevent productive age.